The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5830/cvja-2011-057
|View full text |Cite
|
Sign up to set email alerts
|

The time-course changes of NT-proBNP and tissue Doppler indices in patients undergoing mitral valve replacement

Abstract: BackgroundIn severe mitral regurgitation, a subset of patients who are asymptomatic may develop left ventricular decompensation before changes in echocardiographic parameters become evident. Since N-terminal brain natriuretic peptide (NT-proBNP) is used to detect early heart failure, we hypothesised that NT-proBNP would be activated in patients with mitral regurgitation.MethodsPatients submitted to surgery were prospectively evaluated over eight months in the Department of Cardiology at Inkosi Albert Luthuli C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[7] Under these circumstances mitral valve replacement is associated with higher morbidity and mortality due to advanced LV impairment. [9] None of our seven patients in the group with the EF 40-49% (median EF 42%) underwent mitral valve repair which is recommended under these circumstances. The choice of the surgical procedure was dependent on the available expertise at our centre to carry out MV repair which is technically difficult in RHD compared to non-rheumatic MR.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…[7] Under these circumstances mitral valve replacement is associated with higher morbidity and mortality due to advanced LV impairment. [9] None of our seven patients in the group with the EF 40-49% (median EF 42%) underwent mitral valve repair which is recommended under these circumstances. The choice of the surgical procedure was dependent on the available expertise at our centre to carry out MV repair which is technically difficult in RHD compared to non-rheumatic MR.…”
Section: Discussionmentioning
confidence: 84%
“…shown that patients with severe mitral regurgitation frequently presented late; many were in heart failure, beyond the optimal period for surgical intervention as judged by the echocardiographic parameters and confirmed on natriuretic peptide estimation. [9] However, this study did not describe the outcome of subjects undergoing surgery for rheumatic MR who have impaired LV function, since few patients had overt impairment of LV function [9].…”
Section: Rhd: Rheumatic Heart Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) levels increased among all moderate or severe chronic MR. It has already shown that in MR, changes in volume load may be paralleled by changes in the N-terminal brain natriuretic peptide (NT-proBNP) level and that the fall in NT-proBNP was related to corrections in volume and removal of the diastolic run-off into the left atrium [45] , [46] . However there are no data on the relationship between levels of ANP, BNP, NT-proBNP and atrial strain in patients with mitral regurgitation.…”
Section: Correlation Between Left Atrial Strain and Left Atrial Dysfumentioning
confidence: 99%